Hegel's dialectic : five hermeneutical studies - Gadamer, Hans-Georg, 1900-2002 (Yale University Press, 1976)
Tracing the development of the notion of the dialectic from the classical Greek thinkers to the modern thinkers, Gadamer demonstrates that Hegel 'worked out his own dialectical method by extending the dialectic of the Ancients.' Excellently translated, this book is a valuable if demanding addition to Gadamer's philosophical work now available in English. These five essays on Hegel give the English-speaking reader a long-awaited opportunity to read the work of one of Germany's most distinguished philosophers, Hans-Georg Gadamer. Gadamer's unique hermeneutic method will have a lasting effect on Hegel studies.